Development of Learning Media for Writing Pantun Based on Mobile Learning Using WordPress Content Management System - Lusi Intani; Mohammad Ilyas; Bibit Suhatmady (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2023)
Insufficient vocabulary and a lack of learning resources/references that offer pantun examples and variants make it difficult for students to write pantun. Researchers make a learning media product that makes it easier for students in the form of websites that contain material for writing pantun. This research was conducted with the objectives of: (1) to produce learning media based on mobile learning in the form of a pantun writing learning media website. (2) carrying out learning to write pantun using mobile learning-based media using WordPress Content Management System (CMS). (3) determine the effectiveness of the use of mobile learning-based learning media using WordPress CMS on pantun writing Material. The method used is a research and development model adapted from Sugiyono, namely with ten steps: potentials and problems, data collection, product design, design validation, design revision, product trial, product revision, trial use, revision, and mass product. Instruments in data collection activities are observation sheets, media needs questionnaires, validation sheets, student pantun writing test results, and interest in learning sheets. Data collection was accomplished using of field observations, interviews, and questionnaires. Additionally, analyses of the curriculum, needs, and students were completed. The result of the research revealed that mobile learning-based pantun writing learning media is appropriate and effective for learning to write pantun for seventh grade students of junior high school. This learning media can be used as a resource for students to learn on their own and make the learning process more interesting and efficient.